Intellectual Capital Disclosure: The Effect of Family and Non-Executive Directors on Board - Kamardin, Hasnah; Abu Bakar, Robiah; Ishak, Rokiah (American Scientific Publishers, 2017)
The study examines the effect of corporate governance characteristics on the intellectual capital (IC) disclosure in public listed companies in Malaysia.Samples of the companies are 55 companies from the top 100 companies in 2006 based on market capitalization.Data are collected for 2 years (2006 and 2011).The t-test analysis shows that IC disclosure is found more in big size companies, high leverage companies, government-link companies (GLC), and high-tech companies. Results from the regression analysis show that family members on board are negatively related to IC disclosure.This finding is consistent with previous studies that family firms prefer less voluntary disclosure.Further analysis with each component of IC shows that foreign ownership is positively related to structural capital and non-executive directors are positively related to human capital disclosure. This result somehow supports the important role of non-executive directors and foreign ownership to reduce the information asymmetry between managers and shareholders.